CEA to peritoneal carcinomatosis index (PCI) ratio is prognostic in patients with colorectal cancer peritoneal carcinomatosis undergoing cytoreduction surgery and intraperitoneal chemotherapy: A retrospective cohort study. Issue 4 (19th December 2017) - Kozman, Mathew A.; Fisher, Oliver M.; Rebolledo, Bree‐Anne J.; Parikh, Roneil; Valle, Sarah J.; Arrowaili, Arief; Alzahrani, Nayef; Liauw, Winston; Morris, David L.
Abstract : Background and Objectives: Serum tumor markers are prognostic in patients with colorectal cancer peritoneal carcinomatosis (CRPC) undergoing cytoreductive surgery (CRS) and intraperitoneal chemotherapy (IPC). Assessment of the ratio of tumor marker to volume, as depicted by peritoneal carcinomatosis index (PCI), and how this may affect overall (OS) and recurrence free survival (RFS) has not been reported. Methods: Survival effect of this ratio was analyzed in patients with CRPC managed from 1996 to 2016 with CRS and IPC. Results: Of 260 patients included, those with low CEA/PCI ratio (<2.3) had longer median OS (56 vs 24 months, P  = 0.001) and RFS (13 vs 9 months, P  = 0.02). The prognostic impact of CEA/PCI ratio was most pronounced in patients with PCI ≤ 10 (OS of 72 vs 30 months, P  < 0.001; RFS of 21 vs 10 months, P  = 0.002). In multivariable analysis, elevated CEA/PCI ratio was independently associated with poorer OS (adjusted HR 1.85, 95%CI 1.11‐3.10, P  = 0.02) and RFS (adjusted HR 1.58, 95%CI 1.04‐2.41, P  = 0.03). Conclusion: CEA/PCI ratio is an independent prognostic factor for OS and RFS in CRPC. This novel approach allows both tumor activity and volume to be accounted for in one index, thus potentially providing a more accurate indication of tumor biological behavior.